Unusual scapular winging – A case report. (August 2016) - Dori, Zohar; Sarig Bahat, Hilla
Abstract: Scapular mobility has a central role in maintaining normal upper limb function. Scapular winging is characterized by a failure in the dynamic stabilization of the scapula against the thoracic wall resulting in a condition in which the medial border of the scapula is prominent. The following case describes a patient who was referred to physiotherapy due to abnormal scapular protrusion. The main findings of the physical examination showed weakness of the scapular stabilizers more prominent on the right side than of the left. Additionally, the physical examination demonstrated weakness of the abdominal muscles, hip adductors, and ankle dorsi-flexors, as well as some facial muscles. The electromyography results were inconclusive. Further examination led to clinical suspicion of Facioscapulohumeral Dystrophy (FSHD) as a diagnosis, which was confirmed by genetic testing. Facioscapulohumeral Dystrophy is characterized by symptoms related to motor function and in most cases becomes evident in patients in their 20s and 30s. The disease signs and symptoms are often identified in a clinical setting. Currently, there are no reports describing an effective treatment for the disease. However, physiotherapy, moderate physical exercise, counselling, and use of suitable aids and orthoses may help improve functionality and mobility. This case report aims to increase the awareness of musculoskeletal physiotherapists to this unique dystrophy, when encountering complex presentations with scapular winging. Highlights: When scapular winging presents with abdominal weakness, facial muscles should be assessed. Spread out weakness around various body regions should question muscle dystrophy. The classic clinical sign of Facioscapulohumeral Dystrophy is the 'Beevor's sign'. The physiotherapist may be a key clinician in the diagnosis and treatment of patients with FSHD. Physiotherapists should provide therapeutic guidance regarding proper training, and suitable aids/orthoses.